2022
DOI: 10.1108/jfra-10-2021-0382
|View full text |Cite
|
Sign up to set email alerts
|

Political connections, financing decisions and cash holdings: empirical evidence from Gulf Cooperation Council

Abstract: Purpose This study aims to investigate the relationship between political connections, financing decisions and cash holding. Design/methodology/approach Based on historical data from 181 active non-financial firms listed on Gulf Cooperation Council (GCC) Stock Exchange Markets during the period of 2009–2016, this study uses ordinary least squares and dynamic system-generalized method of moments to test the research hypotheses. The final data set comprises a total of 1,448 firm-year observations from ten majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 147 publications
0
13
1
Order By: Relevance
“…(2020), who revealed that government ownership has a negative relationship with the total debt ratio. Tawfik et al . (2022) found negative impacts of the presence of royal family members in BDs and debt financing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2020), who revealed that government ownership has a negative relationship with the total debt ratio. Tawfik et al . (2022) found negative impacts of the presence of royal family members in BDs and debt financing.…”
Section: Resultsmentioning
confidence: 99%
“…Company ownership in GCC countries has historically been concentrated in the hands of royal families and governments; thus, royal family members are on BDs or in high management positions (Al-Razeen and Karbhari, 2004; Sidani and Al Ariss, 2014; Alzahrani and Che-Ahmad, 2015). Tawfik et al . (2022) and Ding et al .…”
Section: Theoretical Literature and Hypothesis Developmentmentioning
confidence: 99%
“…The controls include firm size (SIZE), leverage (LEV), research and development expenditures (R&D), cash holding (CASH), liquidity (QUICK), firm loss (LOSS) and profitability (ROA). We also follow Tawfik et al (2022) and include the gross domestic product (GDP) and inflation rate (INF) as country-level control variables. Appendix A provides detailed definitions and sources of information for all variables.…”
Section: Methodsmentioning
confidence: 99%
“…Financial distress refers to a situation whereby a company cannot generate sufficient cash to meet or pay its financial obligations which, if not well controlled, may lead to bankruptcy. As such, the presence of a high level of cash within a firm enables the company to avoid liquidity problems, meet its investment opportunities and minimise the costs associated with external financing by increasing the flexibility of internal financing (Al-Dhamari and Ismail, 2015; Eulaiwi et al , 2018; Tawfik et al , 2022). A review of the literature indicates that an effectively performing IC can assist the firm to hoard an optimal level of cash (Al-Hadi et al , 2020; Eulaiwi et al , 2018) to improve its investment efficiency (Eulaiwi et al , 2020), thereby improving the firm’s value (Al-Matari, 2019).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation